ChemInform Abstract: Regioselective 1, 4‐Conjugate Hydrocyanation of Dienones Using Potassium Hexacyanoferrate(II) as an Eco‐Friendly Cyanide Source. Issue 4 (January 2015) - Li, Zheng; Yin, Junjun; Li, Tianpeng; Wen, Gong; Shen, Xiaoli; Yang, Jingya
Abstract A novel method for the regioselective hydrocyanation of dienes (I) is developed using non‐toxic K4[Fe(CN)6] as the cyanide source.